Prehypertension in adolescents with cardiovascular risk: a comparison between type 1 diabetic patients and overweight subjects. (December 2016) - Giacchi, Valentina; Timpanaro, Tiziana; Presti, Donatella; Passanisi, Stefano; Mattia, Carmine; Betta, Pasqua; Grasso, Chiara; Caruso, Manuela; Sciacca, Pietro
Abstract Background Adolescents with type 1 diabetes and obesity present higher cardiovascular risk and ambulatory blood pressure measurements (ABPM) has been shown to predict vascular events, especially by identifying the nondipper status. The aim of our observational cross-sectional study conducted in adolescents with type 1 diabetes, overweight subjects and healthy controls was to assess mean blood pressure parameters to identify subclinical cardiovascular risk. Methods The study included adolescents patients with type 1 diabetes followed in our Pediatric Department in University of Catania between January 2011 and 2013. A total of 60 patients were enrolled, and 48 (32 male and 16 female) completed the study. For each subject we performed systolic and diastolic Ambulatory Blood Pressure Measurements (ABPM) during wakefulness and sleep recording blood pressure every 30 min for 24 h with the Tonoport V/2 GE CardioSoft V6.51 device. We compared the data of patients with those of overweight subjects and healthy controls. Results ABPM revealed no significant difference between type 1 diabetic patients and overweight subjects in 24 h Systolic, 24 h Diastolic, Day-time Systolic, Night-time systolic and Day-time Diastolic blood pressure values but significantly different values in Night-time Diastolic blood pressure values (p < 0.001). We found significant differences between type 1 diabetic patients and healthy controls in all 24 h Systolic (p < 0.001), 24 h Diastolic (p < 0.01), Day-time Systolic (p < 0.01), Night-time Systolic (p < 0.001), Day-time Diastolic (p < 0.05) and Night-time Diastolic (p < 0.001) blood pressure values. We detected hypertension in 12/48 (25 %) type 1 diabetic patients and in 10/48 overweight subjects (p = 0.62; OR 1.2; CI 0.48–3.29), whereas no-one of healthy controls presented hypertension (p < 0.001). We observed nondipper pattern in 40/48 (83.3 %) type 1 diabetic patients, in 33/48 (68.8 %) overweight subjects (p = 0.094; OR 2.27; CI 0.85–6.01), and in 16/48 (33.3 %) of healthy controls (p < 0.001; OR 10; CI 3.79–26.3). Conclusions ABPM studies might help to define a subset of patients at increased risk for the development of hypertension. In evaluating blood pressure in type 1 diabetes and overweight subjects, ABPM should be used since a reduced dipping can indicate incipient hypertension.